A proteção jurídica do meio ambiente no Brasil e a eficácia dos instrumentos processuais - Botelho, Tiago Resende (2011)
In Brazil the right to an ecologically balanced environment is the conquest of the Federal Constitution of 1988, when passing, to be interpreted as a fundamental human right of common use and essential to a healthy quality of life. In singing, the environment, get fuzzy guise of law, where any human being is possessed of the fundamental right to an ecologically balanced environment, to the point of the constitutional legislator, granting a duty to defend and preserve this fundamental right of third dimension to the Government and the community. Consequently, this new reading of the environment, puts the state and community as actors responsible for the protection of ecologically balanced environment, and for this, have to their disposal, the following instruments: class action, injunction, civil action and writ of mandamus. Each has its merits, but all with one aim, effect Article 225 of the Constitution. It happens that, by the grandeur and seeking experienced environmental crisis and protect the legal instruments are interpreted by a significant portion of society as legally ineffective. Ideas that this work deconstructs and chasing. It's that musty above instruments have numerous limitations and in no way seeks only boasts them, closing their eyes to their shortcomings, however, balancing the two sides of this debate will show that even with the existing limitations, and exist, these instruments are characterized as a commitment to a viable and civilized solution to protect the ecologically balanced environment. Therefore, through the analysis of individual procedural instrument, will reach the conclusion that they are legally effective instrument for ensuring the right to an ecologically balanced environment.